1999
DOI: 10.1128/jcm.37.6.2093-2098.1999
|View full text |Cite
|
Sign up to set email alerts
|

PCR Amplification from Fixed Tissue Indicates Frequent Involvement of Brachyspira aalborgi in Human Intestinal Spirochetosis

Abstract: PCR procedures amplifying portions of the 16S rRNA and NADH oxidase genes of Brachyspira aalborgi and Serpulina pilosicoli were applied to DNA extracted from paraffin-embedded human colonic or rectal tissues from 30 Norwegian, Australian, and U.S. patients, 16 of whom had histologic evidence of intestinal spirochetosis (IS). B. aalborgi-specific sequences were identified by PCR in 10 of the IS patients (62.5%) but none of the others, while S. pilosicoli sequences were not detected in tissues from any patient. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 42 publications
0
45
2
Order By: Relevance
“…Studies using enzymatic and genetic analysis have shown that there are several species of intestinal spirochetosis. Mikosza et al [6] reported the organism to be related to Brachyspira aalborgia, which is probably non pathogenic in the immunocompetent patient, however, a study to Trivett-Moore et al [7] suggested Serpulina pilosicoli to be the agent in patients with symptomatic spirochetosis. The latter organism showed attachment of a phenotypically and genotypically distinct weakly beta haemolytic intestinal spirochete to the brush border of colonic enterocytes suggesting enteropathogenecity [10] and the same organism has been shown to be enterotoxic in animal models resulting in watery diarrhoea [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using enzymatic and genetic analysis have shown that there are several species of intestinal spirochetosis. Mikosza et al [6] reported the organism to be related to Brachyspira aalborgia, which is probably non pathogenic in the immunocompetent patient, however, a study to Trivett-Moore et al [7] suggested Serpulina pilosicoli to be the agent in patients with symptomatic spirochetosis. The latter organism showed attachment of a phenotypically and genotypically distinct weakly beta haemolytic intestinal spirochete to the brush border of colonic enterocytes suggesting enteropathogenecity [10] and the same organism has been shown to be enterotoxic in animal models resulting in watery diarrhoea [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…While some authors suggest that the organism is non pathogenic, others have shown clinical manifestations of symptoms such as diarrhoea and a clinical response to antimicrobial therapy [4,5]. No common organism has been cultured in a large number of cases of spirochetosis, but a Brachyspira aalborgi specific sequence was detected by PCR in 62.5% of patients with spirochetosis [6]. In another study Serpulina pilosicoli was recovered from rectal biopsies in 50% of symptomatic patients with a histological diagnosis of intestinal spirochetosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…A 471 base pair sequence of the 16S rRNA gene of B. aalborgi, equivalent to the base pair positions 172^675 of the 16S rRNA gene of Escherichia coli, was targeted for PCR ampli¢cation, as described previously [4], except that dimethyl sulfoxide was not added. Furthermore, the 16S rRNA gene of B. pilosicoli was targeted for PCR ampli¢cation as described previously [4], except that a di¡erent reverse primer (5P-CCCCTACAATATCCAAGACT-3P) was used. This produced a 439 bp product equivalent to the base pair positions 204^676 of the 16S rRNA gene of E. coli [16].…”
Section: Polymerase Chain Reactionsmentioning
confidence: 99%
“…Two species of anaerobic intestinal spirochaetes, Brachyspira (formerly Serpulina) pilosicoli [1] and Brachyspira aalborgi [2], colonise the human large intestine [3,4]. Both species are associated with a condition known as intestinal spirochaetosis (IS), in which a thin carpet-like layer of spirochaetes is found attached by one cell end to the colorectal surface epithelium [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation